Correlation between the Mechanical Properties and Laser-Induced Breakdown Spectroscopy for Human Teeth - Dakhil, Suhad .S.; Hamad, Tagreed .K. (Iraqi Journal of Science, 2024)
The present study investigates the correlation between mechanical properties and laser-induced breakdown spectroscopy (LIBS) for different tooth samples. A set of Fourteen samples collected from the Al-Kut Specialized Dental Centre in Wasit Governorate was analysed. Tooth samples were divided into groups depending on age and gender (men, women). The optical emission of the ionic-to- atomic intensity ratio of the Ca spectral line has been correlated with Leeb hardness test (LHT) values, compressive strength, and Young’s modulus measured by standard tools. The ratio ionic line to atomic line CaII / CaI between the ionic calcium line at 396.84 nm and the atomic line at 558.87 nm for teeth is obtained using LIBS technique employing Nd: YAG laser with a wavelength of 1064 nm, an energy of 200 Mj, and a pulse duration of 10 ns. A linear relationship was observed between compressive strength, Young’s modulus and hardness, and the concentrations of the elements (Ca). The small relative errors for hardness, compressive strength, and Young’s modulus ranged from (1.44-5.57) %, (1.94-6.07) %, and (0.243-4.01) %, respectively. These findings validate applying LIBS to check out some important mechanical properties.